Hero, Charity Case, and Victim: How U.S. News Media Frame Military Veterans on Twitter. Issue 4 (October 2019) - Parrott, Scott; Albright, David L.; Dyche, Caitlin; Steele, Hailey Grace
Commenters often criticize the mass media for providing audiences a narrow and inaccurate representation of U.S. military veterans. This study examined the claim by researching how regional news publications in the 50 states represented veterans on Twitter. A quantitative content analysis documented the presence or absence of characteristics in 1, 460 tweets that employed the terms veteran or veterans. Data were examined using cluster analysis. Three frames emerged. The most prevalent frame, labeled charity, highlighted instances in which veterans received assistance from charitable organizations and others. The second frame, hero, contained references to honor, World War II, and content that would elicit pride from audience members. The third frame, victim, highlighted the mistreatment of veterans by the military and/or society, mental health issues, politics, and the Gulf War. Results suggest U.S. news consumers are provided a narrow representation of what it means to be a veteran.